2009
DOI: 10.1016/j.tifs.2008.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Bananas, raw materials for making processed food products

Abstract: Musa spp., comprising banana and plantain, are among the world's leading fruit crops. Worldwide, 103 million tonnes were produced in 2004, according to FAO statistics database. Few bananas produced undergo industrial processing. Plantain and unripe banana are consumed cooked, whereas, mature dessert banana is eaten raw. Characterising bananas, their processed products and processed consumption forms, is a key precondition for objective communication on these foodstuffs. This will enable niche markets for this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
242
1
18

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 375 publications
(294 citation statements)
references
References 59 publications
(61 reference statements)
9
242
1
18
Order By: Relevance
“…Obtaining banana flour Green (stage 2 of ripening: all green) (AURORE et al, 2009) Cavendish (Musa acuminate) banana was purchased from a local supermarket in Belém, Pará, Brazil. The fruits were washed and separated into two lots: one containing the whole fruit (pulp and peel) and the other only the pulp.…”
Section: Methodsmentioning
confidence: 99%
“…Obtaining banana flour Green (stage 2 of ripening: all green) (AURORE et al, 2009) Cavendish (Musa acuminate) banana was purchased from a local supermarket in Belém, Pará, Brazil. The fruits were washed and separated into two lots: one containing the whole fruit (pulp and peel) and the other only the pulp.…”
Section: Methodsmentioning
confidence: 99%
“…The unripe plantain was considered to be stage 2 (Aurore, Parfait, & Fahrasmane, 2009) and was bought from a market at Cuautla, Morelos, México, and the flour was obtained by using the procedure of Ovando-Martínez et al (2009). Chickpea flour, white corn flour and semolina were purchased at the establishment, Giusto's Vita-Grain of San Francisco, California, USA.…”
Section: Raw Materialsmentioning
confidence: 99%
“…The consumption of fruits and vegetables has been inversely associated with morbidity and mortality from degenerative diseases (Terry et al, 2001). Aurore et al (2009) reported that banana, an herbaceous climacteric fruit, represents one of the most significant fruit crop in world export trade after coffee, cereals, sugar and cocoa and is one of the most important fruit crops grown throughout Kerala (Shanmughavelu et al, 1992). Bananas are one of the most popular food in the world contain various antioxidant compounds such as gallocatechin and dopamine which protects the body against the ill effects of free radicals.…”
Section: Introductionmentioning
confidence: 99%